Putting the Mystical Mind Together - Newberg, Andrew (Zygon, 2001)
This article reviews and responds to various issues that have been raised in critical analysis of our work studying the relationship between religion and the brain. An adequate response necessitates a discussion about the origins of this research, the potential pitfalls of doing empirical research in this field, and the complex requirements of interpreting the implications of such an approach. Through inquiry such as this, the study of the brain and its relation to religion and religious experience will continue to advance and uncover the many fascinating questions that await.